Does early-targeted risk-based management of a patent ductus arteriosus improve outcomes in preterm infants? Insights from an observational study - Orla Franklin; Sean Armstrong; Naomi McCallion; Aisling Smith; Rachel Mullaly; Afif EL-Khuffash; Claire Murphy; Lyudmyla Zakharchenko (BMJ Paediatrics Open, 2025)
Background This study evaluates the outcomes of an early-targeted patent ductus arteriosus (PDA) management strategy in preterm infants using the EL-Khuffash PDA Severity Score (PDAsc) for risk stratification. The objective was to compare outcomes between high- and low-risk infants from an early-targeted treatment epoch and a historical reference epoch who were risk stratified but did not undergo treatment.Methods We conducted a single-centre, observational cohort study in a level III neonatal intensive care unit. Infants born <29 weeks gestation were stratified into high- and low-risk groups using the PDAsc. High-risk infants in the early-targeted treatment epoch received medical intervention, while low-risk infants did not. Outcomes from this epoch were compared with a historical reference epoch in which risk was assigned but treatment was not implemented. The primary outcomes included chronic lung disease (CLD), ventilation days and oxygen days.Results A total of 110 high-risk and 74 low-risk infants were identified in the early-targeted epoch, compared with 84 high-risk and 51 low-risk infants in the reference epoch. High-risk infants in the early-targeted treatment epoch who achieved successful PDA closure demonstrated fewer ventilation days (median 5 vs 11), fewer oxygen days (median 45 vs 65) and a lower incidence of CLD (59% vs 76%) compared with high-risk infants in the reference epoch. However, high-risk infants in the early-targeted treatment epoch who failed treatment experienced outcomes similar to high-risk infants in the reference epoch. Low-risk infants in both epochs exhibited comparable favourable outcomes.Conclusions The implementation of early-targeted risk-based PDA management may be associated with improved respiratory outcomes in high-risk infants who successfully responded to treatment. However, the observational nature of this study limits causal inferences. These findings underscore the need for further research, including randomised controlled trials with improved patient selection, to better understand the relationship between stratified treatment and important outcomes.